2019
DOI: 10.3390/ijerph16132415
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being and Romantic Relationships: A Systematic Review in Adolescence and Emerging Adulthood

Abstract: Adolescence and emerging adulthood are both stages in which romantic relationships play a key role in development and can be a source of both well-being and negative outcomes. However, the limited number of studies prior to adulthood, along with the multiplicity of variables involved in the romantic context and the considerable ambiguity surrounding the construct of well-being, make it difficult to reach conclusions about the relationship between the two phenomena. This systematic review synthesizes the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(124 citation statements)
references
References 169 publications
6
108
1
9
Order By: Relevance
“…The prevalence of offline DV victimization in adolescents is high, especially the psychological-emotional victimization [30][31][32][33][34][35]. Offline DV victimization in a romantic relationship negatively affects adolescents' well-being and has been related to stress, anxiety, less satisfaction with life, poor academic achievement, low self-esteem, substance abuse, and eating disorders [30,31,33,36,37]. Positive correlations among different forms of offline DV victimization (physical, verbal-emotional, and relational) have been observed [38], and it has also been suggested that being victimized in one social context increases the probability of being victimized in other social contexts, which could increase the possibility of suffering poly-victimization [39][40][41][42][43][44].…”
Section: Offline and Cyber Dating Violence Victimizationmentioning
confidence: 99%
“…The prevalence of offline DV victimization in adolescents is high, especially the psychological-emotional victimization [30][31][32][33][34][35]. Offline DV victimization in a romantic relationship negatively affects adolescents' well-being and has been related to stress, anxiety, less satisfaction with life, poor academic achievement, low self-esteem, substance abuse, and eating disorders [30,31,33,36,37]. Positive correlations among different forms of offline DV victimization (physical, verbal-emotional, and relational) have been observed [38], and it has also been suggested that being victimized in one social context increases the probability of being victimized in other social contexts, which could increase the possibility of suffering poly-victimization [39][40][41][42][43][44].…”
Section: Offline and Cyber Dating Violence Victimizationmentioning
confidence: 99%
“…The author describes a family organization characterized by an intrusive, intolerant, and hypercritical mother and by a father who is often brilliant but absent from the family. In this type of environment, where there is no real emotional support, the patient expresses her discomfort through an abnormal and provocative eating behavior, which on the one hand allows her to obtain a form of control and self-affirmation in her relationship with her family, but on the other hand leads her to a further confirmation of her position of dependence and loneliness [47,48].…”
Section: The Relational-systemic Paradigm: Family Relationships In Eamentioning
confidence: 99%
“…Moreover, emerging adults engage in a variety of social interactions related to work and love life [17,18,41]. Therefore romantic relationships can be an important source of well-being for emerging adults [51]. However, the satisfaction of an intimate relationship is associated with empathy [5254].…”
Section: Introductionmentioning
confidence: 99%